2022
DOI: 10.1029/2021jd035951
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5‐Bound Polycyclic Aromatic Hydrocarbons (PAHs), Nitrated PAHs (NPAHs) and Oxygenated PAHs (OPAHs) in Typical Traffic‐Related Receptor Environments

Abstract: Fine particulate matter (PM 2.5 , aerodynamic diameter of ≤2.5 μm) has attracted worldwide attention in recent years due to its adverse effect on ambient air quality and public health (Chen et al., 2019;Cohen et al., 2017;van Donkelaar et al., 2015). Owning to their small particle size and large surface area, PM 2.5 can act as carriers for many chemical substances and reach bronchus, alveolar spaces, and even blood, which can seriously harm human health (Kroll et al., 2013;Poschl, 2005;Shou et al., 2019). A mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…9-NANT was the main congener detected in the samples from both Seoul and Ulaanbaatar. It has been reported that 9-NANT is emitted from direct sources, predominantly diesel engines, and is also formed in the atmosphere as a result of secondary reactions [ 43 , 44 ]. Ulaanbaatar generally uses biomass fuel and coal fuel (lignite) for household cooking and heating It is an urban area with high levels of PM and PAH pollution because of the use of solid fuels [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9-NANT was the main congener detected in the samples from both Seoul and Ulaanbaatar. It has been reported that 9-NANT is emitted from direct sources, predominantly diesel engines, and is also formed in the atmosphere as a result of secondary reactions [ 43 , 44 ]. Ulaanbaatar generally uses biomass fuel and coal fuel (lignite) for household cooking and heating It is an urban area with high levels of PM and PAH pollution because of the use of solid fuels [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Ulaanbaatar, the concentration of PAHs is high, and this causes high concentrations of NPAHs and OPAHs because of secondary formations. Additionally, the main causes for the primary emissions of NPAHs in urban regions are diesel engine vehicles and incomplete combustion by residential heating [ 44 ]. As biomass combustion is the main source of OPAHs [ 46 ], biomass and heating fuel-use in Ulaanbaatar could contribute to high NPAH and OPAH concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The number of rings of PAHs were showed in Table S2 in Supporting Information S3. Before analysis, three pretreatment processes were applied following our previous work (Fang et al, 2019;Wang et al, 2022), as described in the Text S3 in Supporting Information S1.…”
Section: Emission Factor Calculationmentioning
confidence: 99%
“…For example, the relatively high contribution of both 3-and 4-ring hydrocarbons in the particulate phase (>70%) was observed on 25 May (VD = SE, WS = 2.6 m s −1 ), 16 June (VD = SE, WS = 3.6 m s −1 ), 17 June (VD = SE, WS = 3.4 m s −1 ), 13 July (VD = SE, WS = 1.8 m s −1 ), 14 July (VD = SE, WS = 1.9 m s −1 ), 15 July (VD = SE, WS = 2.6 m s −1 ), and 16 July (VD = SE, WS = 2.4 m s −1 ), indicating that in particular low-and medium-molecular-weight organic compounds could be partly attributed to emission from local shipping activities. Recent studies on coastal PM chemical composition in some regions of Asia [32] and Europe [33] also demonstrated that particles of various size modes can be considerably influenced by anthropogenic emissions from sources such as shipping activities.…”
Section: Distribution Of Particle Pah Compoundsmentioning
confidence: 99%